Pemanfaatan Daun Kesambi dalam Ransum Berbahan Dasar Rumput Lapangan dan Pengaruhnya terhadap Pertumbuhan Kambing Lakor - INSUN SANGADJI; HENY E TAHYALA (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
The research was conduccted in Yoiha sub-village Letti District at Maluku Barat Daya regency for two months. The objective of the research was to study growth of Lakor goat fed native grass basal diet with kesambi leaf, specifically, this research was aimed to determine percentage of kesambi leaf and its effects on Lakor goat growth. The research was arranged into a Simple Randomized Design with five treatments and three replications. Kesambi Leaf was offered at 25%, 50%, 75% and 100% to subtitute native grass. The measurements were feed intake, avarage daily gain and feed efficiency. The results showed that using kesambi leaf 50%, 75% and 100% had significant effect (P